Monster with a thousand heads [videorecording (DVD)] - Raluy, Jana; Aguirre, Sebastian; Albores, Hugo; Santullo, Laura, 1970- (Music Box Films, 2016)
When Sonia receives the news that her husband's cancer has progressed to a terminal stage, she races to secure the insurance company approval for the care that can help him. Met with indifference and negligence at every turn, Sonia's desperation triggers a primal survival instinct as a series of increasingly violent confrontations unfold. A sharp, urgent tale of a distraught woman intent on protecting her family at all costs.